Angular Dependence of Solar Cell Parameters in Crystalline Silicon Solar Cells Textured with Periodic Array of Microholes. Issue 9 (4th June 2020) - Altinoluk, Serra; Kumar, Naveen; Ciftpinar, Emine Hande; Demircioglu, O.; Turan, Rasit; Vasileska, Dragica
Abstract: Surface texturing is an indispensable way of increasing absorption in solar cells. In order to properly characterize the effect of texturing, the angular dependence of the incidence light should be addressed. This is particularly important when the actual application where the incidence angle of the sunlight varies during the day is considered. This study presents the angular dependence of solar cell parameters in the case of periodically textured crystalline silicon (c‐Si) solar cells with microholes. A standard solar cell with pyramid texturing is also studied for comparison. It is shown that the incidence angle for the highest efficiency depends on the surface structure. While a standard pyramid‐textured surface performs best at the zero angle of incidence, it is needed to tilt the sample with microholes textures 15° with respect to the surface normal. This is also confirmed by the simulation study performed for the structures presented in this study. Abstract : The efficiency of a solar cell strongly depends on the properties of the interaction between the incoming light beam and the surface of the device. This study shows the angular dependence of performance in a solar cell with various surface texture patterns. It is concluded that for each surface pattern there exists a different tilt, resulting in maximum cell performance.